Should performance-enhancing drugs in sport be legalized under medical supervision? - Wiesing, U. (Sports Medicine, 2011)
This review examines the question of whether performance-enhancing drugs should be permitted in sport under the control of physicians, and evaluates the expected outcomes of such a scenario. Such a change in regulation would need to be tightly controlled because of the risks involved. The results of legalizing performance-enhancing drugs in competitive sport would be either unhelpful or negative, and the unwanted aspects of doping control would not disappear. Athletes, including children and adolescents who wanted to pursue competitive sports, would be forced to take additional, avoidable health risks. The `natural lottery` of athletic talents would be compensated for only partially by use of performance-enhancing agents. It would also be complemented by another `natural lottery` of variable responses to doping measures, combined with the inventiveness of doping doctors. There would be no gain in `justice` (i.e. fairer results that reflected efforts made) for athletes as a result of legalizing doping. Legalization would not reduce restrictions on athletes' freedom; the control effort would remain the same, if not increased. Extremely complicated international regulations would have to be adopted. The game of the`tortoise and the hare` between doping athletes and inspectors would remain because prohibited but not identifiable practices could still provide additional benefits from use of permissible drugs. Audience mistrust, particularly toward athletes who achieved outstanding feats, would remain because it would still be possible that these athletes were reliant on illegal doping practices. Doping entails exposing the athletes to avoidable risks that do not need to be taken to increase the appeal of a sport. Most importantly, the function of sport as a role model would definitely be damaged. It is not necessary to clarify the question of what constitutes the `spirit of sport` and whether this may be changed. From a practical point of view, a legalization of performance-enhancing drugs in sport should not be considered for the simple reason that it has no advantages but many disadvantages.